Wake-up call for HPPP – health promotion, prevention, and preparedness - Lev, Vered; Ron, Aviva (Frontiers in Public Health, 2023)
The latest public health emergencies exposed urgent gaps in health promotion, prevention and preparedness (HPPP). Existing and new infectious diseases have gained far more prevalence than expected, and inequities in access to health care accounted for disturbing differences in the toll of these diseases in different populations. The COVID-19 pandemic not only demonstrated the need to prevent the onset and progression of non-communicable chronic diseases (NCDs) and promote healthy lifestyles, but also the need to prepare for new infectious diseases and their long-term effects on both physical and mental health. Preparedness was previously associated with natural disasters, with activities directed to developing emergency humanitarian action response resources. However, these actions are inadequate for the frequent natural disasters as the climate crisis intensifies. To reach effective actions in HPPP, we take a broad approach to HPPP components, identify the main stakeholders and suggest methods to change allocations for HPPP. We propose a call for action at global and national levels, involving strengthening the United Nations’ Sustainable Development Goals and government commitment to HPPP.